Nights: Rome, Venice, in the Aesthetic Eighties; London, Paris, in the Fighting Nineties - Pennell, Elizabeth Robins, 1855-1936 (Salt Lake City, UT : Project Gutenberg, 2008)
"Nights: Rome, Venice, in the Aesthetic Eighties; London, Paris, in the Fighting Nineties" by Elizabeth Robins Pennell is a memoir written in the early 20th century. The book explores the life and experiences of the author as she navigates through various European cities, reflecting on the artistic and cultural currents of the time. The narrative is rich with encounters that reveal the personalities of notable figures and the vibrant art scene of the era, highlighting both the uniqueness and universality of human experiences. At the start of the memoir, the author reminisces about her early days of travel and work in Europe, specifically noting her first arrival in Rome with her husband, J. She reflects on their struggles with their limited means and the misadventures that ensued, such as their experiences with the police for riding a tricycle and getting lost in the Ghetto. The narrative effectively sets the scene for the adventures that follow, detailing their determination to embrace life despite the hardships, and provides a glimpse into the artistic milieu that would come to shape their time in Rome and beyond. The opening chapter weaves nostalgia and a sense of wonder as the couple finds beauty in their artistic ambitions, enriched by the vibrant backdrop of European culture. (This is an automatically generated summary.)
Release date is 2008-01-29
E-text prepared by Paul Dring, Suzanne Shell, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Rome (Italy) -- Description and travel; Venice (Italy) -- Description and travel; London (England) -- Description and travel; Paris (France) -- Description and travel